Learning to live with COVID-19 in Australia: time for a new approach - Catherine M Bennett (Sax Institute, 2021)
The emergence of the Delta variant of SARS-CoV-2 has made Australia's 'COVID-zero' strategy unviable. As signalled by the Australian Government's National plan to transition Australia's national COVID-19 response, we need to plan a pathway forward for life beyond lockdown. However, this plan must be guided by long overdue discussions on our tolerance for serious illness, and hospital and intensive care unit capacity. The modelling that informs the national transition plan remains relevant, even with increases in case numbers, but one crucial thing that does change if cases continue to escalate is the effectiveness of test, trace and isolate models. As we move into suppression mode with higher rates of the population fully vaccinated, we will no longer need to find every case. This is among the many shifts in approach that will shape our transition by early 2022 to living with - and controlling - the disease.